Optical and Microstructural Characterization of Thin Layers - Łukasz Skowroński (Crystals, 2020)
The microstructure and optical properties of layers strongly depend on the method of synthesis. This Special Issue on “Optical and Microstructural Characterization of Thin Layers” is a collection of papers on the relationships between the growth conditions and specific properties of thin films.